Non-invasive hemodynamic monitoring as a guide to drug treatment of uncontrolled hypertensive patients: effects on home blood pressure in the BEAUTY study. (2nd November 2018) - Talvik, Anneli; Rebora, Paola; Heinpalu-Kuum, Marika; Salerno, Sabrina; Miszkowska-Nagórna, Eliza; Liu, Xiaoqiu; Comotti, Tommaso; Świerblewska, Ewa; Valsecchi, Maria Grazia; Fadl Elmula, Fadl Elmula M.; Larstorp, Anne Cecilie; Narkiewicz, Krzysztof; et al.
Abstract: Background: In the BEAUTY study we investigated whether utilizing non-invasive monitoring of hemodynamic parameters combined with a drug selection algorithm (integrated hemodynamic management-IHM) compared to conventional drug selection may improve home BP in patients with uncontrolled hypertension. Methods: Uncontrolled (office systolic blood pressure (SBP) > 140 mmHg and ambulatory daytime SBP >135 mmHg while taking ≥2 antihypertensive drugs) essential hypertensive patients were referred to 5 European Hypertension Excellence Centers and, if eligible, were randomized into IHM-guided vs conventional treatment adjustment. Home blood pressure (BP) was taken with 2 repeated readings at 1–2 min intervals in the morning and in the evening (before drug intake and eating) during the week preceding the visit at the outpatient clinic after 5 min rest using a validated semi-automatic oscillometric arm cuff device and with a correct cuff bladder placement. Home blood pressure was measured in a sub-group of patients ( n = 84) not significantly different from the other patients. Results: Home SBP changed from 152.1+/−15.8 and 149.8+/−11.8 mmHg to 131.0 +/−11.1 and 139.6+/−12.8 mmHg in IHM group ( n = 46) and Control group ( n = 38), respectively, showing significantly greater reduction in IHM than in Control group (d= −10.9 mmHg, 95% CI −17.77, −4.02), p = 0.002. The reduction remained significant after multiple adjustments, particularly for baseline home SBP, recruiting center, age, sex and BMI (SBPIHM-Control = −9, 63 mmHg, 95% CI −14.28, −5.11) mmHg, p < 0.0001). Conclusion: Drug selection algorithm based on non-invasive hemodynamic monitoring induced larger reduction in home BP compared to conventional drug selection in uncontrolled hypertensive patients referred to European Hypertension Excellence Centers. Although the main BEAUTY study was negative, these home BP measurements taken by patients themselves may suggest that the integrated hemodynamic monitoring is useful in patients with uncontrolled hypertension. This finding might depend on specific features of home BP measurements which could make it recommended BP measurement method for drug trials.